Augmented reality applied to the restoration of historical heritage - Ortiz-Zamora, Francisco José; Ladrón-de-Guevara-Muñoz, María del Carmen; Miravet-Garret, Laia; Pérez-García, Jorge; Martín-Domínguez, Rafael; Salgado-Fernández, Javier; Lora Núñez, Ángel (DYNA, 2022)
Spain occupies a prominent position among the countries with the most UNESCO World Heritage Sites. The possibilities offered by the application of AR-VR technologies for some of these elements’ virtual reconstruction brings a great opportunity to give visibility and support the transmission of cultural heritage, especially in those cases where physical restoration is not possible. It is increasingly common to find virtual reconstructions of monuments, since these do not damage either put at risk the element being represented. In this work, the process of modelling and reconstructing the Castillo de la Estrella, located in the town of Teba (Malaga), as well as the subsequent development of an Augmented Reality application is presented. This allows the Castillo de la Estrella reconstruction to be displayed virtually on mobile devices such as smartphones or tablets, and might potentially be implemented in the museum that houses the castle itself, providing a tool that improves the visitor experience and completes the range of cultural activities carried out in the monument
Keywords: Realidad virtual; Augmented Reality; Virtual Reality; Historical Heritage; 3D Modelling